Fear of cancer recurrence in young women 5 years after diagnosis with a good-prognosis cancer: the VICAN-5 national survey - Magnani, Clément; Smith, Allan Ben; Rey, Dominique; Sarradon-Eck, Aline; Préau, Marie; Bendiane, Marc-Karim; Bouhnik, Anne-Déborah; Mancini, Julien (Journal of cancer survivorship, 2023)
Purpose Fear of cancer recurrence (FCR) is frequent in survivors, but less is known about FCR in long-term survivors with very low risk of relapse. Our aim was to estimate the prevalence and clinical and socio-behavioural factors associated with FCR in young women 5 years after diagnosis of a good-prognosis cancer. Methods Using data from the VICAN-5 survey, conducted in 2015–2016 amongst a national representative French sample of cancer survivors, we included women with non-metastatic melanoma, breast, or thyroid cancer, aged 55 years or under at diagnosis, who experienced no disease progression in the 5 years post-diagnosis. Multinomial logistic regression was used to identify factors associated with FCR, characterised using a three-level indicator: no, mild, and moderate/severe FCR. Results Amongst the 1153 women included, mean age was 44 years at diagnosis, and 81.8% had breast cancer, 12.5% thyroid cancer, and 5.8% melanoma. Five years after diagnosis, 35.4% reported no FCR, 46.0% mild FCR, and 18.6% moderate/severe FCR. Women with thyroid cancer were less likely to suffer from mild or moderate/severe FCR, while cancer-related treatment sequelae, fatigue, and anxiety were more likely. Limited health literacy was associated with mild FCR. Women who reported only occasionally consulting a general practitioner (GP) for the management of their cancer had a higher probability of FCR. Conclusion Moderate/severe FCR affected nearly 20% of young female long-term survivors diagnosed with a good-prognosis cancer, particularly those reporting cancer-related sequelae, suffering from fatigue or anxiety, with breast cancer or melanoma (versus thyroid cancer), and consulting a GP only occasionally for cancer management. Implications for Cancer Survivors Given the recognised impact of FCR on quality of life, it is essential to detect it as early as possible, and to implement targeted interventions in routine care.